The extreme centre a warning - Ali, Tariq (London Verso, 2015)
What is the point of elections? The result is always the same: a victory for the Extreme Centre. Since 1989, politics has become a contest to see who can best serve the needs of the market, a competition now fringed by unstable populist movements. The same catastrophe has taken place in the US, Britain, Continental Europe and Australia.
Includes bibliographical references and index.
Keywords: World politics -- 1989-; World politics -- Forecasting; Center parties -- Western countries; Democracy -- Western countries; Political culture -- Western countries; Capitalism -- Political aspects -- Western countries